Rozwój public relations w krajach Wspólnoty Niepodległych Państw - Bekbołatuły, Żetpisbaj (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The paper outlines the emergence, development and the current status of the public relations sector in the Commonwealth of Independent States (CIS) using the example of its evolution in three member states of the CIS: Russia, Ukraine and Kazakhstan. It discusses the specificity of the PR market that emerged after the collapse of the USSR in the three former republics that are most significant for this sector. The process of establishment of the first PR agencies, both domestic and the branches of the largest foreign agencies, is described. The paper discusses the problems the PR market faced and continues to struggle with in these three states. Additionally, the development of education in this field is presented, as well as the numerous obstacles that hinder this process in these countries.